Algunos prólogos de Pedro Garfias - García Monge, Carlos (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
In this article which briefly reviews the critical work of Pedro Garfias, three texts of the author written in Mexico and not gathered so far in the collections of his work are presented. These are two critical nature prose writings appeared in 1940 and 1941, and a short poem which was used in 1956 to preface the first book of the Mexican writer Margarita Villaseñor.
Keywords: Pedro Garfias; spanish literature of exile; unpublished texts; Margarita Villaseñor